2005
DOI: 10.1089/neu.2005.22.623
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Standard Trauma Craniectomy for Refractory Intracranial Hypertension with Severe Traumatic Brain Injury: A Multicenter, Prospective, Randomized Controlled Study

Abstract: To compare the effect of standard trauma craniectomy (STC) versus limited craniectomy (LC) on the outcome of severe traumatic brain injury (TBI) with refractory intracranial hypertension, we conducted a study at five medical centers of 486 patients with severe TBI (Glasgow Coma Scale score Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(176 citation statements)
references
References 16 publications
2
165
1
8
Order By: Relevance
“…The investigators found significantly greater mortality in patients with a limited craniectomy 60 . A second study in China compared 1-month mortality, complications and the 1-year GOS score of larger unilateral decompressive craniectomy with routine unilateral temporoparietal decompressive craniectomy.…”
Section: Chinamentioning
confidence: 96%
“…The investigators found significantly greater mortality in patients with a limited craniectomy 60 . A second study in China compared 1-month mortality, complications and the 1-year GOS score of larger unilateral decompressive craniectomy with routine unilateral temporoparietal decompressive craniectomy.…”
Section: Chinamentioning
confidence: 96%
“…This is important, for example, because of various trials conducted in mainland China that have shown beneficial effects of decompressive craniectomy, hypothermia, and progesterone. 10,[12][13][14][15] These were all well-designed, high-quality studies. However, it is conceivable that differences may exist in referral policies, potential for selection bias, access to health care, acute and post-acute treatments, and outcome.…”
Section: Clinical Trials In Tbi: Past Experiencementioning
confidence: 99%
“…Within few hours after injury or ischemia pressure of edematous temporal lobe on brain stem will cause necrotic changes within the stem and along the cranial nerves and vascular structures [7] therefore additional craniectomy along the temporal fossa is a crucial part of decompression technique in order to relieve pressure on temporal lobe as a whole hence on brain stem. A large bony decompression also reduces the incidence of delayed intracranial haematoma, repeated surgical intervention, postoperative CSF leakage, traumatic seizure(s), and/or intracranial infections [10]. In our series three patient had minimal brain strangulation: one patient (patient #2) underwent bilateral F-T-P craniectomy; and he had full recovery (GOS score, 5).…”
Section: Discussionmentioning
confidence: 56%